Khilafah Islamiyah (Kajian Historis dan KemungkinanKemungkinannya) - Ghafur, Saiful Amin (Tasamuh: Jurnal Studi Islam, 2016)
Terminology Caliphate is something that is familiar to us primarily Muslims who religiously based education, where the term is for the first time drawn from Khulafaurrasyidin period, indicating the Islamic government, up to several times, also associated with the reign undertaken by the dynasty Rasyidah khulafa after dynasty rule. Islamic government caliphate was pioneered by the Prophet, and the khulafaurrasyidin. In the concepts of Islamic thought, it is proper to get attention, because only with such systems compatibility between religion and political sectors can work in harmony. In accordance with the times, religion called for human beings always setting the social system in accordance with the conditions along the corridor and not injuring the religious teachings